Die Verwendung von 2-Chlormethylpyridin-N-oxiden in Cycloadditionen mit isolierten Doppelbindungen - Martin Riediker; Walter Graf (CHIMIA)
It is shown that heterocyclic tetraenes of type 3 and 4, generated from chloromethyl-pyridine N-Oxides (cf. 1) and epoxyvinylpyridine N-oxides (cf. 2) resp., give raise to [8 + 2]-cycloadducts with isolated, olefinic double bonds (cf. 5 and 6) together with their respective substitution products (cf. 11 and 12). The cycloadducts 5 and 6 can be converted into ring opened products (cf. 9 and 10) by bond-isomeric cycloreversion (cf. 7 and 8) induced by proton abstraction with DBU.